The complete mitochondrial genome of Anas crecca (Anseriformes: Anatidae) - Qin Zhang; Ying Wang; Renrui Chen; Birong Liu; Xianzhao Kan (Mitochondrial DNA. Part B. Resources, 2017)
The complete mitochondrial genome of Anas crecca is 16,596 bp in length. It was predicted to contain 13 PCGs, 22 tRNA genes, and 2 rRNA genes, and a putative control region. All of the PCGs initiate with ATG, except for MT-CO1, MT-CO2, and MT-ND5, which began with GTG. Four types of termination codons were identified. Phylogenetic analysis shows that A. crecca clustered with Anas acuta, and the monophyly of the genera Anser, Cygnus, Aythya, and Anas was strongly supported. Moreover, our results also support a sister-group relationship between Anas and Aythya.